Strategi public relation untuk mengelola krisis pada perusahaan - Dzakirah, Nabilah Mutiara (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze public relations (PR) strategies in managing crises in companies. A crisis can arise suddenly and has the potential to damage a company’s reputation and operations. Therefore, an effective PR strategy is needed to overcome the crisis and minimize its negative impacts. The method used in this research is a literature study from various journals and scientific articles related to crisis management and PR strategies. The research results show that effective PR strategies in managing crises include: pre-crisis preparation and planning, forming a crisis management team, transparent and consistent communication, use of social media, collaboration with key opinion leaders, and post-crisis evaluation. Implementing this strategy can help companies restore their reputation and rebuild public trust after the crisis.